Pelaksanaan Kegiatan Posyandu Balita pada Masa Pandemi Covid-19 sebagai Upaya Pemenuhan Hak Balita sesuai dengan Peraturan Menteri Kesehatan No 4 Tahun 2019 - Swasti Artanti; Pedvin Ratna Meikawati (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
One of the efforts to produce quality human resources (HR) is to reduce morbidity and mortality of children under five. The development of the quality of human resources by optimizing the potential for growth and development of children can be carried out evenly, if a community-based health service system such as posyandu can be carried out effectively and efficiently and can reach all targets that need services such as child growth and development, pregnant women, breastfeeding mothers and postpartum mothers. . Posyandu is a form of Community Based Health Efforts (UKBM) which is managed and organized from, by for and with the community in the implementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services to accelerate the reduction of maternal and infant mortality. The purpose of this study was to determine the relationship between mother's level of knowledge and age of toddlers with visits by mothers with toddlers to the new normal era posyandu in Pekalongan city. This research was conducted using a descriptive correlative research method with a cross sectional approach, sampling with a saturated sampling technique with a total of 37 mothers who have toddlers 1-5 years. The instrument used was a questionnaire sheet and the analysis used was Chi Square statistical test. Based on the results of univariate analysis, most of the children who visited the posyandu were aged 3 years, namely 10 children (31.2%), with parental education as many as 22 respondents (68.8%) having higher education (PT), dominated by working parents as many as 24 children (75%). A total of 25 respondents (78.1%) visited the posyandu regularly and most of the respondents had a good level of knowledge, as many as 29 respondents (20%). The results of the bivariate analysis showed that there was no relationship between children's age and posyandu visits (p value 0.217) and there was a relationship between parents' knowledge level and posyandu visits (p value 0.002). It is hoped that parents who have children aged 1-5 years will continue to routinely bring their children to the posyandu in the new normal era even though they still apply health protocols.